Bibliographic database of the Conservation Information Network : BCIN - Conservation Information Network (1987)
[Dt.:] BCIN ist die weltweit größte bibliographische Online-Datenbank für Konservierung und Restaurierung des Getty Institutes. - [Engl.:] BCIN, the Bibliographic Database of the Conservation Information Network, is the Web's most complete bibliographic resource for the conservation, preservation and restoration of cultural property.